Paleomagnetism and magnetic fabrics of the Almopias, Thessaly and Milos volcanics. Implications for the regional deformation - ATZEMOGLOU, A.; KONDOPOULOU, D.; ZANANIRI, I. (Bulletin of the Geological Society of Greece, 2001)
New palaeomagnetic and rock magnetic data obtained from the plio-quaternary volcanics in Almopias (NW Greece) are presented, together with existing ones from two other localities (Thessaly and Milos) in the Aegean extensional area. In most cases a stable component, slightly deviated from the expected direction, has been identified. Rock magnetic analysis reveals the presence of either magnetite (Thessaly), hematite (Milos) or both (Almopias) The anisotropy of magnetic susceptibility reaches significant levels for only part of the samples whereas the anisotropy ellipsoid could be defined in only one case (Almopias). The existing structural data for the three areas, together with fault plane solutions provide a representative deformation pattern. Comparison of -small- rotation angles and possible rotation of the stress field has been possible in the case of Almopias.